PENGARUH KUALITAS PRODUK, SOCIAL MEDIA MARKETING DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK RETAIL CIBO CENTRAL KITCHEN - I Putu Yoga Pratama Putra; Ni Putu Cempaka Dharmadewi Atmaja; Daniel Manek (Jurnal Bakti Saraswati (JBS), 2025)
Cibo Central Kitchen, located in Denpasar, Bali, faces challenges in increasing consumer purchasing decisions amidst intense competition in the food and beverage industry. This research aims to evaluate how product quality, social media marketing, and brand image influence consumer purchasing decisions. The main focus of this research is to understand how these three factors can increase consumer appeal and loyalty toward the products offered. This research uses a quantitative approach with a survey method. Data was collected thru questionnaires distributed to Cibo Central Kitchen consumers using a purposive sampling technique, involving 180 respondents. Data analysis was conducted using multiple linear regression to identify the influence of product quality, social media marketing, and brand image on purchasing decisions. The analysis results indicate that product quality, social media marketing, and brand image significantly and positively influence consumer purchasing decisions. Product quality improvements, such as innovation, taste, and freshness; the use of appropriate social media marketing strategies; and a solid brand image, are able to attract interest and increase consumer loyalty. Therefore, it is recommended that Cibo Central Kitchen continue to innovate its products, increase interaction thru social media, and maintain a positive brand image to strengthen its competitiveness in the market